Waste cotton Fabric/MXene composite aerogel with heat generation and insulation for efficient electromagnetic interference shielding. Issue 10 (15th May 2022) - Zhai, Jianyu; Cui, Ce; Li, Ang; Guo, Ronghui; Cheng, Cheng; Ren, Erhui; Xiao, Hongyan; Zhou, Mi; Zhang, Jinwei
Abstract: Electromagnetic interference (EMI) shielding materials have become more and more indispensable due to serious electromagnetic-radiation pollution. Herein, waste cotton cellulose aerogels were prepared by dissolving waste cotton fabrics (WCF) in NaOH/urea aqueous solution, and MXene nanosheets were subsequently deposited on the cellulose aerogels by a facile dip coating method to obtain WCF/MXene composite aerogels. The WCF/MXene composite aerogels with highly porous network structure show remarkable electrical conductivity (8.2 Ω/sq of surface resistance), high EMI shielding effectiveness (EMI SE) in the range of 2–18 GHz (39.3–48.1 dB). The WCF/MXene aerogel possesses high SSE and SSE/t of 677.94–829.74 dB cm 3 g −1 and 3512.62–4299.17 dB cm 2 g −1, respectively (2–18 GHz). In addition, the heating temperature of WCF/MXene composite aerogels reaches 199 °C when 3 V positive voltage is applied on them. The WCF/MXene composite aerogels possess excellent electromagnetic shielding effectiveness, heat generation property and insulation, which can be potentially used as multifunctional materials for EMI shielding, electrical-heating and high temperature protection.